Pengaruh Profitabilitas, Kebijakan Dividen dan Keputusan Struktur Modal Terhadap Nilai Perusahaan (Study Pada Perusahaan Manufaktur Sektor Aneka Industri yang terdaftar di Bursa Efek Indonesia (BEI) Periode 2016-2018) - Mikael Oki; Sugeng Haryanto; Vinus Maulina (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2019)
This research was conducted to examine the effect of profitability, dividend policy and capital structure decisions on the value of companies listed on the Indonesia Stock Exchange (IDX) 2016-2018 period. The population used in this study is manufacturing companies in various industry sectors which are listed on the Indonesia Stock Exchange (IDX). The sampling technique in this study used purposive sampling. The results showed that profitability has a significant effect on firm value, dividend policy and capital structure decisions have no influence on firm value.